Hidradenitis Suppurativa is Associated with Non-alcoholic Fatty Liver Disease: A Cross-sectional Study - Iris González-Villanueva; Cristina DeGracia; Mariana Planells; Inés Poveda; Pedro Álvarez; Luca Schneller-Pavalescu; Isabel Betlloch; Gregor B.E. Jemec; Jose M. Ramos; Jose C. Pascual (Medical Journals Sweden, 2020)
Non-alcoholic fatty liver disease (NAFLD) is currently the most common cause of end-stage liver disease. The aim of this controlled cross-sectional study was to assess the association between NAFLD and hidradenitis suppurativa. NAFLD was assessed using hepatic ultrasound. A total of 125 patients with hidradenitis suppurativa and 120 patients without hidradenitis suppurativa were recruited, matched for age, sex and body mass index (< 25 or > 25 kg/m2), a risk factor related to NAFLD. Both groups presented similar proportions of overweight or obesity (89.6% vs 90%). Patients with hidradenitis suppurativa presented significantly higher prevalence of NAFLD compared with those with non- hidradenitis suppurativa (57.6% vs 31.7%, p < 0.001). Multivariable analysis confirmed independent association between hidradenitis suppurativa and NAFLD (odds ratio 2.79, 95% confidence interval 1.48-5.25; p = 0.001) besides age, body mass index, hypertension and hypertransaminasaemia. Hidradenitis suppurativa is significantly associated with the development of NALFD regardless of the presence of classic metabolic risk factors.